Neuroimaging and neuropsychological findings in pediatric obsessive–compulsive disorder: a review and developmental considerations. (August 2012) - Abramovitch, Amitai; Mittelman, Andrew; Henin, Aude; Geller, Daniel
SUMMARY Obsessive–compulsive disorder (OCD) is one of the most prevalent psychiatric disorders affecting children and adolescents. In the last decade, our knowledge base of pediatric OCD has increased greatly. In examining pediatric OCD, neuropsychological performance may serve as a bridge between brain functioning and the phenomenology of the disorder. Recent advances in neuropsychological and neuroimaging techniques have led to significant interest in the neurobiological underpinnings of OCD. Although considerable research has been conducted on adults with this disorder, relatively little research has been directed towards similarly afflicted youth. Neurobiological research including lesion, structural and functional imaging studies are reviewed, along with the literature on neuropsychological testing and deficits associated with the disorder. Emphasizing both the neural and cognitive developmental processes within the pediatric population, these findings are examined and critiqued within a developmental framework.